2015
DOI: 10.1007/s10967-015-4528-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of deuteron-induced reactions on natGd up to 30 MeV: possibility of production of medically relevant 155Tb and 161Tb radioisotopes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Their physical characteristics are listed in table 5 and the production cross sections values are presented in table 6 and in figures 2 to 10. Our new production cross section results are, in general, in good agreement with the values published by Tárkányi et al, 2014, andSzelecsényi et al, 2016. The TALYS code shows some disagreements excepted for Tb-153, Tb-156g and Tb-160, for which the TALYS 1.6 Adj values give an overall good agreement with the experimental points.…”
Section: The Tb-155 Contaminants Production Cross Sectionssupporting
confidence: 90%
See 1 more Smart Citation
“…Their physical characteristics are listed in table 5 and the production cross sections values are presented in table 6 and in figures 2 to 10. Our new production cross section results are, in general, in good agreement with the values published by Tárkányi et al, 2014, andSzelecsényi et al, 2016. The TALYS code shows some disagreements excepted for Tb-153, Tb-156g and Tb-160, for which the TALYS 1.6 Adj values give an overall good agreement with the experimental points.…”
Section: The Tb-155 Contaminants Production Cross Sectionssupporting
confidence: 90%
“…Our experimental production cross section points are plotted as full circle in figure 1, compared with the work of Tárkányi et al, 2014 andSzelecsényi et al, 2016, and with the results of the TALYS 1.6 code. Our experimental values, obtained in the energy range from 10.5 to 33.3 MeV, show different bumps in agreement with the reaction routes leading to the Tb-155 production: 2n) with E threshold = 3.88 MeV, 3n) (E threshold = 12.52 MeV) and 4n) Szelecsényi et al, 2016, measured from 4 to 21 MeV, show the same trend as our points with higher values but also in agreement within their error bars. The TALYS code results using default models give a first maximum at 23 MeV, in disagreement with the experimental one, which is close to 25 MeV.…”
Section: The Tb-155 Production Cross Sectionmentioning
confidence: 98%
“…Alternative methods of producing these isotopes have been investigated (Table 2) 815 . However, full-scale production at a radionuclide purity sufficient for clinical studies has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Subatomic particles such as neutron, proton, deuteron, 3 He, 4 He, and other heavier particles are generated and then accelerated to certain energies sufficient for production of radioisotopes. At thermal energy, neutrons can be directed into a target to create radioisotopes relevant for nuclear medicine applications, such as 154 Sm, 166 Ho, 149 Pm, 166 Ho, 161 Tb, and 177 Lu [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…At thermal energy, neutrons can be directed into a target to create radioisotopes relevant for nuclear medicine applications, such as 154 Sm, 166 Ho, 149 Pm, 166 Ho, 161 Tb, and 177 Lu [1,2]. Deuteron particles accelerated in circular accelerators or cyclotrons have been recently employed to produce short-lived medical radioisotopes such as 44m Sc, 44g Sc, 155 Tb, and 161 Tb [3,4], whereas 3 He particles have been suggested for production of 44m,46m+g,47,48 Sc, 48 V, and 48 Cr radioisotopes [5].…”
Section: Introductionmentioning
confidence: 99%